Moral Frameworks for Leaders of Gifted Programs and Services. Issue 2 (3rd April 2017) - Brown, Elissa F.; Rinko-Gay, Catherine
Abstract : Given the complexities of being an educational leader and, specifically, an educational leader of a gifted program or school, should there be a moral guide or framework that can inform the daily practices of leaders within an ever-changing educational context of competing demands? Should leaders of gifted programs employ the same ethos as any leader or by virtue of leading a program of a special interest group, be guided by a different, moral approach? This article posits that leaders of gifted programs and schools should operationalize an integrated approach drawing upon a variety of historical and more current theories of moral reasoning and intuition coupled with theories that draw on distributive, transformational, and situational leadership in order to make their advocacy and leadership more effective.